Cochlear Implants and Magnetic Resonance Imaging: Experience With Over 100 Studies Performed With Magnets in Place. Issue 1 (January 2021) - Fussell, Wanda L.; Patel, Neil S.; Carlson, Matthew L.; Neff, Brian A.; Watson, Robert E.; Lane, John I.; Driscoll, Colin L. W.
Abstract : Objective: To evaluate adverse events and feasibility of performing 1.5-T MRI in patients with cochlear implants (CI) and auditory brainstem implants (ABI). Setting: Single tertiary academic referral center. Patients: CI and ABI recipients undergoing 1.5-T MRI without internal magnet removal. Intervention(s): MRI after tight headwrap application. Main Outcome Measures: Adverse events, patient tolerance. Results: A total of 131 MR studies in 79 patients were performed, with a total of 157 study ears. Sixty-one patients (77%) had unilateral devices. Four patients (5%) underwent MRI with ABI magnets in place. Sixteen patients (20%) had MRI-compatible devices that did not require a head wrap. There were no instances of device stimulation, device malfunction, or excessive heating of the receiver-stimulator package. Magnet tilt requiring manual repositioning occurred during seven studies (4.5%) and magnet displacement requiring operative intervention occurred during seven studies (4.5%). Significant pain where imaging had to be discontinued occurred during three episodes (2%). No adverse events were noted among patients who underwent MRI with an MRI-compatible magnet. Conclusions: MRI with CI or ABI magnets in place is associated with a low prevalence of adverse events when performed in a controlled setting. Many partial magnet displacements can be corrected with firm manual pressure. Devices with magnets that align with the field within their housing were not associated with any adverse events and do not require immobilization of the magnet during the scan. These may be valuable in patients with known or anticipated need for MRI.